Allergen Immunotherapy (AIT) in children: a vulnerable population with its own rights and legislation – summary of EMA‐initiated multi‐stakeholder meeting on Allergen Immunotherapy (AIT) for children, held at Paul‐Ehrlich‐Institut, Langen, Germany, 16.1.2019. Issue 1 (29th June 2020) - Mahler, V.; Mentzer, D.; Bonertz, A.; Muraro, A.; Eigenmann, P.; Bousquet, J.; Halken, S.; Pfaar, O.; Jutel, M.; Wahn, U.; Vieths, S.; Kaul, S.
Abstract: Concerning development of medicinal products, children belong to a so‐called "special population" for which additional legislation applies: Regulation (EC) No 1901/2006 on medicinal products for paediatric use sets up a system of requirements, rewards and incentives to ensure that medicinal products are researched, developed and authorized to meet the therapeutic needs of children. Allergen Immunotherapy (AIT) is believed to contain a strong potential for immunomodulatory effects inducing sustained clinical efficacy after cessation of treatment (disease modifying effect) and thereby may prevent the progression of the atopic march towards asthma manifestation. However, to this day only few data on long‐term effects in general exist and even fewer in children. These are predominantly data from open studies, which are strongly influenced in their validity by the known placebo effect of AIT. Furthermore, there are no studies allowing for the conclusion that efficacy in adults are mirrored by a similar efficacy in children and thus, up to now, it is not possible to extrapolate data from adults to children. The Paediatric Committee (PDCO)—European Medicines Agency's (EMA) scientific committee responsible for activities on medicines for children—initiated a Multi‐Stakeholder Meeting on AIT for Children held at the Paul‐Ehrlich‐Institut in Langen, Germany, to provide a platform for discussion and exchange of thoughts to this topic between allergy experts from academia, regulators and AIT‐manufacturers. The consented meeting minutes, conclusions and participants are presented.